First Record of Samsama chersonesia chersonesia Distant, 1906 (Hemiptera: Fulgoridae) from Borneo - Abdul Razak, Ahmad Irfan; Siti Nurlydia, Sazali; Ratnawati, Hazali; Fatimah, Abang; Farah Nabillah, Abu Hasan Aidil Fitri (Universiti Kebangsaan Malaysia, 2020)
The only known distribution for the subspecies Samsama chersonesia chersonesia Distant, 1906 was in Perak and Cameron Highlands, Peninsular Malaysia and Sumatra, Indonesia. This paper provides the first distributional record for the subspecies in Sarawak and Sabah, Borneo. A total of 17 individuals were documented based on voucher specimens from three repositories in Sarawak and Sabah, namely Universiti Malaysia Sarawak Insect Reference Collection (UIRC), Research Development and Innovation Division, Forest Department Sarawak (RDID), and Sabah Parks Entomological Museum (SPM). This discovery denotes that this subspecies occurs in Sundaland: Malay Peninsula, Sumatra, and Borneo.